Enhancing medication compliance in schizophrenia through peer support and motivational interviewing - Prasetia, Dwi Indah; Nihyati, Hanik Endang; Kurnia, Iqlima Dwi (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Schizophrenia is a chronic mental disorder that requires long-term and continuous treatment. One of the major barriers to optimal recovery is non-adherence to treatment, which frequently leads to relapse, prolonged hospitalization, and reduced functional outcomes. Psychosocial approaches, particularly peer group support and motivational interviewing (MI), have been widely applied to strengthen treatment adherence. However, a systematic synthesis that integrates the effectiveness of these two interventions has not been well established. Purpose: This systematic review aims to identify and analyze the effects of peer group support and motivational interviewing on improving treatment adherence among patients with schizophrenia. Method: A systematic review approach based on PRISMA guidelines. Article searches were conducted through Scopus, PubMed, and ScienceDirect using the keywords “motivational interviewing”, “peer support”, “medication adherence”, and “schizophrenia”. A total of 1.902.305 articles were identified, and after screening through inclusion and exclusion criteria followed by quality assessment using CASP and the JBI Checklist, 12 studies were selected for final synthesis. Results: Of the 12 included studies, seven used randomized controlled trial (RCT) designs and five used quasi-experimental designs. Most interventions demonstrated significant improvements in medication adherence. Both peer support interventions and motivational interviewing showed positive and consistent effects on enhancing treatment adherence among individuals with schizophrenia. Conclusion: Peer group support and motivational interviewing were found to be effective strategies for increasing treatment adherence in patients with schizophrenia. Short-term interventions delivered intensively can produce meaningful improvements, while longer implementation durations tend to yield more stable outcomes. These approaches are recommended for integration into community-based psychiatric nursing practice.